Elucidating the Calcium-Binding Site, Absorption Activities, and Thermal Stability of Egg White Peptide–Calcium Chelate - Zhijie Bao (MDPI AG, 2021)
With the current study, we aimed to determine the characteristics and calcium absorption capacity of egg white peptide–calcium complex (EWP-Ca) and determine the effect of sterilization on EWP-Ca to study the possibility of EWP-Ca as a new potential calcium supplement. The results of SEM and EDS showed a high calcium chelating ability between EWP and calcium, and the structure of EWP-Ca was clustered spherical particles due its combination with calcium. The FTIR and Raman spectrum results showed that EWP could chelate with calcium by carboxyl, phosphate, and amino groups, and peptide bonds may also participate in peptide–calcium binding. Moreover, the calcium absorption of EWP-Ca measured by the intestinal everted sac model in rats was 32.38 ± 6.83 μg/mL, significantly higher than the sample with CaCl2, and the mixture of EWP and Ca (p < 0.05) revealed appropriate calcium absorption capacity. The fluorescence spectra and CD spectra showed that sterilization caused a decrease in the content of α-helix and β-sheet and a significant increase in β-turn (p < 0.05). Sterilization changed the EWP-Ca structure and decreased its stability; the calcium-binding capacity of EWP-Ca after sterilization was decreased to 41.19% (p < 0.05). Overall, these findings showed that EWP could bind with calcium, form a peptide–calcium chelate, and serve as novel carriers for calcium supplements.